The Impact of Ethical Leadership on Organizational Health of Yemen Company for Flour Mills and Silos in Hodeida Governorate - Zaid, Gamal Dirhim Ahmed; Ali, Dalia Mahmoud Ali (University of Science and Technology Journal for Management and Human Sciences, 2025)
The study aimed to determine the impact of ethical leadership on organizational health in the Yemeni Company for Flour Mills and Silos in Al-Hodeida Governorate. To achieve this goal, a questionnaire was used as the main tool for data collection from a community of 180 individuals. A stratified random sample of 123 individuals was taken, with 105 questionnaires valid for analysis. The data were analyzed using the Statistical Package for the Social Sciences (SPSS). The study concluded with a set of findings, the most important being the positive impact of ethical leadership on organizational health. Ethical leadership has a moderate impact on organizational health in the Yemeni Company for Flour Mills and Silos in Al-Hodeida Governorate. The level of practicing ethical leadership and organizational health in their various dimensions is very high. Based on these findings, the study recommended maintaining the level of ethical leadership through training courses on the importance of ethical leadership and its role in enhancing organizational health in the company. It also recommended maintaining and enhancing the high level of organizational health by continuously providing a suitable environment that ensures the psychological well-being of subordinates.
Keywords: organizational health; ethical leadership; Yemen Company for Flour Mills and Silos